2002
DOI: 10.1021/jp010617i
|View full text |Cite
|
Sign up to set email alerts
|

Size and Band-Gap Dependences of the First Hyperpolarizability of CdxZn1-xS Nanocrystals

Abstract: The first hyperpolarizability of aqueous suspensions of polyphosphate stabilized CdS nanocrystals of different mean sizes and of Cd x Zn1 - x S nanocrystals (x = 0, 0.25, 0.75, 1) was determined by the hyper-Rayleigh scattering technique. We report the first experimental observation that the first hyperpolarizability decreases as the band gap energy increases. This is ascribed to the decrease of the resonance enhancement. The surface modification of 9 nm CdS nanocrystals with OH- increases the first hyperpola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 49 publications
5
90
0
Order By: Relevance
“…[1][2][3][4][5][6] For devices in nanoelectronics and nanophotonics, it is very important to fabricate materials with continuous tunable physical properties. Recent advances in ternary semiconductor nanocrystals or films have shown that their band gaps and then their optical emissions can be tuned by changing their constituent stoichiometries, [7][8][9][10][11][12] while such study is few for the ternary semiconductors with 1D nanostructures.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] For devices in nanoelectronics and nanophotonics, it is very important to fabricate materials with continuous tunable physical properties. Recent advances in ternary semiconductor nanocrystals or films have shown that their band gaps and then their optical emissions can be tuned by changing their constituent stoichiometries, [7][8][9][10][11][12] while such study is few for the ternary semiconductors with 1D nanostructures.…”
mentioning
confidence: 99%
“…The remarkably high sensitivity that we observe in these nanostructures is inherited from the intrinsically large electro-optic tunability of graphene, which offers an extra degree of control to optimize the sensing capability. For comparison, nanographenes present a much higher SHG response than nanoparticles [47] or quantum dots [57,58] of similar size (see SM [56]). As a practical realization, nanographene structures could be passivated with thin insulating layers, which would protect them from undesired chemical interactions (e.g., charge transfer) in the complex environment of the analyte.…”
Section: (B)mentioning
confidence: 99%
“…Moreover, core/shell hetero-NCs with a gradient alloy heterointerface have been shown to possess unique properties, such as reduced Auger recombination rates and lower threshold for amplified spontaneous emission [84]. Alloy QDs and graded interface core/shell hetero-NCs can also be directly synthesized and have attracted increasing interest in the last few years, leading to the investigation of several II-VI and IV-VI compositions [viz., Cd(Te,Se), Cd(S,Se), Pb(S,Se), (Cd,Zn)Se, (Cd,Zn)S, (Cd,Zn)(S,Se)] [80][81][82][83][84][85][86][87][88][89].…”
Section: Composition Effects: Tailoring the Property Gamutmentioning
confidence: 99%